The Role of Caveolin-1 in Intervertebral Disc Degeneration and Regeneration. Issue 1 (April 2016) - Bach, Frances; Zhang, Ying; Verdondschot, Lucy; Bedate, Alberto Miranda; Creemers, Laura; Ito, Keita; Meij, Björn; Sakai, Daisuke; Chan, Danny; Tryfonidou, Marianna
Introduction: During intervertebral disc (IVD) degeneration, the main cell type in the nucleus pulposus (NP) shifts from notochordal cells (NCs) to chondrocyte-like cells (CLCs). Microarray analysis revealed that caveolin-1 expression was correlated with IVD degeneration. The aim of this study was to determine the role of caveolin-1 in NC and CLC physiology to assess its potential role in IVD regeneration. Material and Methods: Protein expression (caveolin-1, apoptosis, progenitor cell markers, extracellular matrix, TGF-β-signaling pathway) was determined in IVDs of wild type (WT) and caveolin-1 knockout (KO) mice and canine IVDs of different degeneration grades (immunofluorescence, immunohistochemistry, TUNEL assay). Micro-aggregate cultures of CLCs from canine and human degenerated IVDs (Thompson grade III) were treated with chondrogenic medium (incl. TGF-β1 ) alone or in combination with (a) caveolin-1 scaffolding domain peptide (CSD) and/or (b) siRNA against caveolin-1. DNA, glycosaminoglycan (GAG) content, collagen type I and II immunohistochemistry and gene expression profiling (RT-qPCR) for extracellular matrix production/degradation-, cell proliferation- and apoptosis markers was performed. Results: The NP of WT mice was rich in viable NCs, whereas the NP of caveolin-1 KO mice contained more collagen type II-rich matrix and less cells together with an increased progenitor cell surface marker (Tie2+/GD2+) expression and a higher apoptotic activity. Caveolin-1 expression increased in the later stages of canine IVD degeneration, together with a significantly increased apoptotic activity. Caveolin-1 knockdown significantly decreased GAG deposition in the CLC aggregates (6–14%), whereas CSD treatment significantly rescued and increased GAG deposition (11–16%). Conclusion: Caveolin-1 plays a crucial role in preservation of NCs, underscored by the NP phenotype of caveolin-1 KO mice. Caveolin-1 may be related with cell senescence given its increased expression in degenerated IVDs. However, caveolin-1 knockdown decreased extracellular matrix production, while CSD supplementation rescued this effect. The latter implies that CSD may be a useful disease modifying agent since it is known to influence degeneration-related signaling pathways (incl. TGF-β signaling). Altogether, this indicates that the increased caveolin-1 expression during IVD degeneration may also be a repair mechanism rather than being merely a senescence marker. Acknowledgment: This work was supported by AOSpine Research Network grants (SRN2011_11, AOSPINE 106540) and the Dutch Arthritis Foundation (LLP22).